1994
DOI: 10.2307/1511183
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept in Children with Learning Disabilities: The Relationship between Global Self-Concept, Academic “Discounting,” Nonacademic Self-Concept, and Perceived Social Support

Abstract: The purpose of this study was to explore how some children with learning disabilities maintain a positive self-concept despite academic difficulties. The study used Harter's model to investigate the relationship between global self-concept and perceived competence in general intellectual ability, specific academic subjects, athletics, behavior and appearance, and perceived social support. Data were collected on 72 elementary-school students with learning disabilities. Five hypotheses were tested: (a) children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
72
1
24

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 19 publications
6
72
1
24
Order By: Relevance
“…Estes resultados são semelhantes aos obtidos por Kloomok & Cosden (1994), que relatam que as crianças com autoconceito negativo apresentam uma menor percepção de suas habilidades intelectuais em comparação com as crianças com autoconceito mais positivo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estes resultados são semelhantes aos obtidos por Kloomok & Cosden (1994), que relatam que as crianças com autoconceito negativo apresentam uma menor percepção de suas habilidades intelectuais em comparação com as crianças com autoconceito mais positivo.…”
Section: Discussionunclassified
“…O reconhecimento das dificuldades acadêmicas e a consideração destas refletem a valorização positiva do domínio acadêmico, o que é concordante com os achados de Kloomok & Cosden (1994). Neste sentido pode-se pensar que um suporte psicopedagógico pode ser bem aceito por estas crianças, uma vez que reconhecem a importância do domínio acadêmico e de suas próprias dificuldades com relação ao mesmo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, reports by the researchers do not all point in the same direction. Thus, whereas one group of studies has shown that students with LD presented lower ability and achievement expectations than their counterparts without LD (Bear, Juvonen, & McInerney, 1993;Chapman, 1988;Gans, Kenny, & Ghany, 2003;González-Pienda et al, 2000;Grolnick & Ryan, 1990;Harter, Whitesell, & Junkin, 1998;Kloomok & Cosden, 1994;Núñez et al, 1995;Rogers & Saklofske, 1985;Stone & May, 2002;Valas, 1999;Vaughn, Elbaum, Schumm, & Hughes, 1998;Vaughn, Haager, Hogan, &Kouzekanani, 1992), another group of studies found no differences in academic self-concept between students with and without LD (Bear & Minke, 1996;Bear, Minke, Griffin, & Deemer, 1998;Dyson, 2003;Meltzer & Montague, 2001;Meltzer, Roditi, Houser, & Perlman, 1998;Montague & van Garderen, 2003;Pintrich, Anderman, & Klobucar, 1994;Priel & Leshem, 1990). With regard to general self-concept, the data provided by past research are more concurrent.…”
Section: Self-conceptmentioning
confidence: 99%
“…Conley et al (2007) reported that students with disabilities do not feel worthless but realize abilities in other areas. Studies have shown that students with disabilities that have fewer academic struggles tend to have a higher perception of themselves (Kistner et al, 1987;Kloomok & Cosden, 1994). Students with learning disabilities have higher self-esteem if they are able to accurately describe personal strengths and areas of weakness (Wilczenski, 1992).…”
Section: Self-concept and Placementmentioning
confidence: 99%